Knowledge and practice of first aid management of epistaxis among parents of under-age children in Hospital USM. - Adnan, Adibah (Universiti Sains Malaysia, 2024)
Epistaxis, commonly known as a nosebleed, is bleeding from the blood vessels in the nose. It is a frequent medical condition that can range from a minor annoyance to a serious medical emergency. The study aims to assess the level of knowledge and practice of first aid management of epistaxis among parents of underage children in Hospital USM. A cross-sectional study was conducted among parents who have underage children. Data was collected using an online self-administered questionnaire. 138 parents attending the Hospital USM and fulfilled the inclusion criteria of this study. They were selected through a convenient sampling method, and the data collected were version 27. The study used descriptive statistics and Pearson Chi-Square. The results show that participants have a high level of knowledge about epistaxis 83(60.1%) and have an average level of practice in first aid management of epistaxis 68(49.3%). There is a significant association between selected demographics and total knowledge of epistaxis regarding gender where the P-value is 0.008. Meanwhile, there is no association between selected demographic factors and total practice of first aid management of epistaxis. As a result, only 18(21.7%) have a high level of knowledge and good practice in first aid management of epistaxis. In conclusion, the assessment of the level of knowledge and practice of first aid management of epistaxis among parents of underage children should be enhanced and improved so that they are more knowledgeable.